2015
DOI: 10.1097/prs.0000000000000918
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the Upper Lateral Cartilage along the Lateral Pyriform Aperture

Abstract: The upper lateral cartilage articulates laterally with the frontal process of the maxilla by means of the pyriform ligament, with a variable amount of overlap between the upper lateral cartilage and maxilla. Relationships among the upper lateral cartilage, maxilla, and pyriform ligament affect the configuration of the lateral internal nasal valve area, and should be considered when planning internal nasal valve reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…They also added that although the anatomical details of the ULCs are of great importance for the maintenance or even the creation of an aesthetically pleasing dorsum with proper respiratory function, the literature includes few studies related to these themes. Crag et al [7] observed that the ULC articulates laterally with the frontal process of the maxilla by means of the pyriform ligament with a variable amount of overlap between the ULC and maxilla. Rohrich and Ghavami [23] on their study on Middle Eastern noses found that the lower lateral, middle and medial crural cartilages are often weak and thin relative to the heavy skin and soft tissue sleeve.…”
Section: Introductionmentioning
confidence: 99%
“…They also added that although the anatomical details of the ULCs are of great importance for the maintenance or even the creation of an aesthetically pleasing dorsum with proper respiratory function, the literature includes few studies related to these themes. Crag et al [7] observed that the ULC articulates laterally with the frontal process of the maxilla by means of the pyriform ligament with a variable amount of overlap between the ULC and maxilla. Rohrich and Ghavami [23] on their study on Middle Eastern noses found that the lower lateral, middle and medial crural cartilages are often weak and thin relative to the heavy skin and soft tissue sleeve.…”
Section: Introductionmentioning
confidence: 99%
“…17 The extensive nature of these fibrous attachments illustrates their important contributions to the ala as well as their functional support of the tip and middle vault. Craig and colleagues 18 showed that the upper lateral cartilages have dense, fibrous attachments to the lateral pyriform aperture. In addition, histological analyses have revealed that the lateral aspects of the upper lateral cartilages lie deep in the frontal process of the maxilla, with a variable degree of distance between the 2.…”
Section: Discussionmentioning
confidence: 99%
“…4,8,19 Even the lateral soft tissue can fall victim to these stresses and, without adequate structural support, can lead to internal nasal valve collapse. 8,18 This outcome underscores the need to evaluate not only the defect location and size but also the extent of tissue elevation required for reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Lateral fibrous attachment of the upper lateral cartilages to the frontal process of the maxilla occurs via bony overlap or close approximation with histological evidence of a pyriform ligament of fused perichondrium with periosteum. 15 Lower pyriform aperture recession contributes not only to an apparent dorsal hump, but also to potential internal nasal valve collapse due to pyriform ligament support loss. The attachments of the upper and lower lateral cartilages at the "scroll" region are composed of unidirectional collagen fibers that are prone to separation and distortion via the forces of facial mimetic muscle movement and the downward force of gravity over time.…”
Section: Bony Facial Skeletonmentioning
confidence: 99%
“…In the ptotic nasal tip, it may be necessary to perform a lateral crural overlay technique where the lateral crura are divided laterally and overlapped to shorten the lateral crural limbs of the tripod complex (►Figs. [15][16][17][18]. This will result in increased nasal tip rotation and shortening of the nose.…”
Section: Managing the Nasal Tipmentioning
confidence: 99%